Ventricular and atrial function in transposition of the great arteries after arterial switch operation - a comprehensive cardiovascular magnetic resonance study. (8th February 2021) - Schuwerk, R; Freitag-Wolf, S; Krupickova, S; Gabbert, D; Uebing, A; Langguth, P; Voges, I
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Although good long-term results after arterial switch operation (ASO) in patients with transposition of the great arteries (TGA) have been described, a few studies suggest that patients can develop ventricular dysfunction. We established a comprehensive cardiovascular magnetic resonance (CMR) analysis protocol to evaluate biventricular and atrial function markers in a large cohort of paediatric and adult TGA patients after ASO. Methods: 103 TGA patients (median age 16.7 years, range 4.3-39.6 years) who underwent ASO were retrospectively included. 66 patients had simple transposition and 37 patients had associated anomalies (ventricular septal defect (VSD) n= 30, aortic coarctation n= 11). 77 healthy subjects were enrolled as controls (median age 15.4 years, range 6.3-43.2 years). Biventricular volumes, wall thickness as well as ventricular and atrial functional and deformation parameters were assessed using standard CMR analyses techniques as well as CMR feature tracking (FT). For statistical analysis each clinical variable was evaluated by standard nonparametrical tests and jointly assessed with machine learning methods (random forest, Boruta). The significant variables were used to build a logistic regression model for predicting the case-control status Results: Results from Mann-Whitney-U test revealed that both, left and right ventricular function markers (left ventricular ejection fraction (LVEF); right ventricular ejection fraction (RVEF); MAPSE; TAPSE; LV long-axis strain) were reduced in patients compared to controls. In addition, left ventricular global longitudinal (-21.18 ± 4.49 / -23.93 ± 3.41; p < 0.001) and circumferential strain values (-29.28 ± 4.30 / -31.32 ± 3.63; p = 0.001) as well as longitudinal strain values for both atria (LA: 24.18 ± 8.04 / 37.81 ± 10.30; p < 0001; RA: 23.89 ± 11.12 / 34.47 ± 10.87; p < 0.001) were lower in patients compared to controls. Segmental FT analysis revealed that the interventricular septum appeared most affected. The logistic regression model demonstrated significant differences for MAPSE, TAPSE (Figure), left atrial global longitudinal strain and basal inferoseptal radial strain. Strong correlations were found between MAPSE and TAPSE (Figure) as well as between left atrial global longitudinal strain and MAPSE (r= 0.54, p < 0.001). Conclusions: TGA patients after ASO are at risk for ventricular and atrial dysfunction. Using a comprehensive CMR analysis protocol along with statistical machine learning methods and a regression approach, we could demonstrate that especially biventricular longitudinal function, left atrial function and basal septal deformation is impaired.